Papel do receptor P2x7 no efeito da toxina a do Clostridium difficile em modelo de alça ileal em camundongos - Santos, Ana Angélica Queiroz Assunção (2017)
Clostridium difficile (C. difficile) is the major cause of colitis associated with the use of antibiotics, with significant morbidity and mortality. The enteric nervous system (ENS) is located in the gastrointestinal tract (GIT) and has an important function of regulating the digestive system. The P2X7 receptor participates in the regulation of cellular permeability, cytokine release and apoptosis, processes that are involved in the pathogenesis of C. difficile induced disease.The aim of this study was to analyze the role of the P2X7 receptor in enteritis induced by C. difficile toxin A (TcdA). The mouse ileal loop was injected with saline (Sodium Chloride 0.9% - Control) or TcdA (50 μg / loop) in mice previously treated with the inhibitors: BBG (50 mg/kg) or A438079 (10 μM) i.p.injection 1 h prior to TcdA (TcdA + BBG; TcdA + A438079) or saline injection. The animals were euthanized after 4h latter and the ileal loop collected for the following analyzes: immunofluorescence for ChAT, NOS, P2X7 and calretinin in membrane preparations, immunohistochemistry for GFAP, HuC / D, S-100β, TUNEL and PCR for P2X7. The results demonstrated that TcdA significantly reduced myenteric plexus neurons in 66.42% when compared to the control, while in the membrane preparations a significant reduction of the immunoreactive neurons to ChAT was observed in 23.21% and Calretinin 28.17%. However, there was a 21.23% increase in labeling for the P2X7 receptor over the control. In the ileal tissue there was an increase of 411.95% and 22.40% respectively in the P2X7 positive area and in the gene expression. In relation to the glial markers, an increase of 125.71% and 144.30% was observed for GFAP and S-100β, respectively. In animals treated with inhibitors P2X7; BBG and A438079, as observed an improvement in histological parameters . In addition , a significant reduction in the number of apoptotic cells decrease in GFAP and S-100β-labeled cells, and cytokines ( TNF-α, IL-1β, IL -6 and IL-8) levels, compared to the control. This was associated with a significant increase in the HuC/D positive area . From these results, it is concluded that TcdA promotes changes in the enteric nervous system, increasing neuronal death and activating glial cells, and that the P2X7 receptor plays an important role in the changes induced by C. difficile TcdA.